Entrepreneurial orientation among college administrators its antecedents and relationships to administrative performance - Nieves, Jesus L.
The level of entrepreneurial orientation of 40 executives from 20 state and 20 private colleges in the Western Visayas were measured with the Rosen Scale and the Entrepreneurial Attitude Scale, supplemented by data on college morale and productivity level gathered from the administrators and 818 college faculty members. The college administrators had moderate levels of entrepreneurial orientation, scoring highest in future orientation and lowest in individualism. No difference in entrepreneurial orientations were found among public and private administrators but the former scored significantly higher in risk taking. Personal and environmental variables were related to entrepreneurial orientation and productivity. Entrepreneurial orientation is positively related to productivity but negatively related to college morale.